Self-Regulated Learning Students With Personalized E-Learning : Siswa Pembelajaran Mandiri Dengan E-Learning yang Dipersonalisasi - Eni Fariyatul Fahyuni; Cindy Taurusta; Ida Rindaningsih; Norhapizah Binti Mohd Burhan; Ihsana El Khuluqo (Academia Open, 2023)
The implementation of personalized e-learning at the Muhammadiyah University of Sidoarjo, especially the Faculty of Islamic Religion, has contributed to this trend of electronic-based learning. The use of e-learning has challenges, namely the need to master digital competence and the responsibilities of lecturers in guiding and directing students during online learning. The analysis used mixed ANOVA to determine the increase in student personalization through e-learning design. the results of the study showed that there were differences in the learning outcomes of the control and experimental groups. The results of the one way ANOVA analysis show differences in personalized learning achievement according to students' learning needs and potential. The more students interact and ask questions outside of class, the more actively they are involved in independent learning from home. This condition is not found in conventional e-learning, which is only carried out modestly by lecturers and students. They create a fun and more communicative learning atmosphere complemented by the reliability of adequate e-learning platform. Highlights: Implementation of personalized e-learning at Muhammadiyah University of Sidoarjo enhances electronic-based learning trend. Challenges include mastering digital competence and lecturer responsibilities in guiding online learning. Mixed ANOVA analysis reveals differing learning outcomes between control and experimental groups. Keywords: Personalized e-learning, Digital competence, Mixed Anova analysis, Independent learning